Về vai trò lãnh đạo của Đảng trong sự nghiệp xây dựng chủ nghĩa xã hội - V.I. Lênin
Về vai trò lãnh đạo của Đảng trong sự nghiệp xây dựng chủ nghĩa xã hội / V.I. Lênin .- H. : Sự thật , 1976 .- 221 tr. ; 19 cm